Combined first principles and Heisenberg model studies of ferrimagnetic Tri-transition quaternary perovskites CaCu3B2Re2O12 (B = Mn, Fe, Co, and Ni). (March 2023) - Mehmood, Shahid; Ali, Zahid; Alwadai, Norah; Al Huwayz, Maryam; Al-Buriahi, M.S.; Trukhanov, S.V.; Tishkevich, D.I.; Trukhanov, A.V.
Abstract: In this study, density functional theory (DFT) showed that the electronic band profiles of CaCu3 B2 Re2 O12 (B = Mn, Fe, Co, and Ni) indicate their half-metallic character. The optimized magnetic energy curves in different magnetic phases demonstrated the type-I ferrimagnetic order of all the compounds investigated in this study. The magnetic exchange coupling constants were calculated between the Cu–B, B–Re, and Cu–Re site spins using the Heisenberg model. These interactions generate strong long range Cu(↑)B(↑)Re(↓) order through a super-exchange mechanism. In these perovskites, the anti-parallel moments of Re with B and Cu reduce the net magnetic moments and they are responsible for the ferrimagnetism. The Cu and B 3d-electrons are localized and responsible for the magnetism, and the Re 5d-electrons are delocalized and responsible for the metallic nature. Magnetic susceptibility analysis verified the results estimated using DFT and the Heisenberg model. Due to the 100% spin polarization around the Fermi level, high Curie temperature TC and ferrimagnetism are expected, thereby making these materials suitable for spintronic applications. Highlights: The half-metallic character of the CaCu3 B2 Re2 O12 (B = Mn, Fe, Co and Ni) was revealed by DFT. Heisenberg model was used for the calculating of the magnetic exchange coupling constants. It has been shown the perspectives of the CaCu3 B2 Re2 O12 (B = Mn, Fe, Co and Ni) in spintronic applications.